The Unresolved Paradox: Critiquing Mu'tazilite and Ash'arite Solutions to Free Will and Divine Justice - Nasra Katiko (Al-Abqori: Journal of Islamic Thought Studies, 2025)
This study critically analyzes and addresses the long-standing theological dilemma in Islamic thought: the two distinct approaches employed by the Mu'tazilite and Ash'arite schools in reconciling human free will and God’s divine justice. Ultimately, it can be argued that neither school fully resolves this complex philosophical and theological dilemma. The objective of this research is to evaluate how each school constructs and defends its position on moral agency while maintaining God’s omnipotence and justice.A comparative analytical methodology is applied by using secondary literature on both schools' theological texts. It dissects their doctrinal systems, such as the Mu'tazilites' emphasis on human agency in producing actions (khalq al-af'al) and the Ash'arite doctrine of acquisition (kasb), to assess their conceptual consistency and practical implications regarding moral responsibility and divine justice. The findings reveal that the Mu'tazilites challenged the concept of absolute divine omnipotence, even as they aimed to defend human moral agency by granting humans’ independent causal power. Meanwhile, the Ash'arites developed the concept of Kasb within their strict endorsement of God's absolute sovereignty. Despite being subtle, this conception can reduce the freedom of will of humans to merely a formal rather than a practical capacity to do an act. Ultimately, neither school proposed an approach that solves the paradox without introducing new theological problems while upholding both divine justice, omnipotence, and human free will. Modern theological discourse could consider alternative conceptions of causality, time, or divine knowledge, or embrace the paradox as an essential feature of the divine-human relationship.